PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA DI BALAI WILAYAH SUNGAI BALI - PENIDA - I Nyoman Tri Gunawan; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (VALUES, 2023)
Job satisfaction is a person's perspective, both positive and negative, about their job. Job satisfaction arises when the employee feels happy because he feels that he has completed an important job and feels that his work is appreciated. Increasing job satisfaction can be seen from organizational culture, leadership style, and empowerment. This study aims to determine and analyze the effect of organizational culture, leadership style, and empowerment on job satisfaction at the Bali-Penida River Basin. The population of this study were 139 employees of the Bali-Penida River Basin Center. The sample of this study was 103 respondents who were determined by the Slovin technique. Data collection was done through interviews, documentation, and questionnaires. The analytical tool used is multiple linear regression analysis which is processed using IBM SPSS version 26 software. The results showed that organizational culture has a positive and significant effect on job satisfaction at the Bali-Penida River Basin. Leadership style has a positive and significant effect on job satisfaction at the Bali-Penida River Basin Center. Empowerment has a positive and significant effect on job satisfaction at the Bali-Penida River Basin Center.